A Study of Emotional Burnout in Teachers Working with Adolescents with Autism Spectrum Disorders - S.M. Valyavko; A.I. Shebalkova (Moscow State University of Psychology and Education, 2023)
In practice of inclusive education teacher emotional burnout is a problem of the critical importance. Working with children with health disabilities requires a high level of competence and is associated with increased cognitive, emotional and communicative load. Emotional burnout is a state of physical, mental and emotional exhaustion that reduces motivation and interest to work. The pilot study was conducted on teachers (N=40) aged 24-55 years in order to study the specifics of emotional burnout in teachers working with adolescents with autism spectrum disorder (ASD) and working with healthy adolescents. The diagnostic methods are: V.V. Boyko «The study of emotional burnout», multifactorial personality questionnaire 16 PF, S. Rosenzweig «The study of frustration reactions». The predominance of emotional burnout in teachers working with ASD has been indicated. Significant correlations of emotional burnout with age, experience and some personal traits have been identified, that can help design a burnout prevention program for teachers, especially while working in the inclusive education system.